2021
DOI: 10.1002/jrsm.1530
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric study of ‘overviews of systematic reviews’ of health interventions: Evaluation of prevalence, citation and journal impact factor

Abstract: Overviews synthesising the results of multiple systematic reviews help inform evidence‐based clinical practice. In this first of two companion papers, we evaluate the bibliometrics of overviews, including their prevalence and factors affecting citation rates and journal impact factor (JIF). We searched MEDLINE, Epistemonikos and Cochrane Database of Systematic Reviews (CDSR). We included overviews that: (a) synthesised reviews, (b) conducted a systematic search, (c) had a methods section and (d) examined a hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…They are growing in number and popularity, and our bibliometric study of the prevalence of overviews found an 8‐fold increase in the number of overviews published between 2009 ( n = 25) and 2020 ( n = 332). 1 The growth in overviews is unlikely to decrease. 1 …”
Section: Introductionmentioning
confidence: 99%
“…They are growing in number and popularity, and our bibliometric study of the prevalence of overviews found an 8‐fold increase in the number of overviews published between 2009 ( n = 25) and 2020 ( n = 332). 1 The growth in overviews is unlikely to decrease. 1 …”
Section: Introductionmentioning
confidence: 99%
“…We will use a database of 1218 overviews published between 1 January 2000 and 30 December 2020 created from a bibliometric study27 as the basis of our search for discordant reviews using Jadad or another method to assess discordance. A validated search filter for overviews28 was used in MEDLINE (Ovid), Epistemonikos and the Cochrane Database of Systematic Reviews (CDSR) for overviews.…”
Section: Methodsmentioning
confidence: 99%
“…As described in our rst companion paper [1], we performed a bibliometric study of overviews published in MEDLINE (Ovid), Epistemonikos, and the CDSR from 2000-2018.…”
Section: Eligibility Criteriamentioning
confidence: 99%